ANALISIS PENERAPAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK DI SD NEGERI PANDU - Ferdinandus, Susan; Rindengan, Mersty Elisabet; Pangkey, Richard Daniel Herdi (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the impact of implementing the Pancasila Student Profile (P5) Project on the character formation of students at SD Negeri Pandu. The study offers a novel integrative exploration that combines locally themed projects with character value reinforcement through exemplary behavior and habituation approaches within the context of elementary education. In contrast to previous studies, which tend to be conceptual, this research empirically examines the practical implementation of P5 through gardening activities involving collaborative participation of teachers, students, school principals, and parents. The gap in prior literature, which has rarely addressed students' spiritual and social dimensions within local elementary school contexts, is addressed through a descriptive qualitative approach employing interviews, observations, and document analysis. The findings indicate that the P5 project has a significant impact on fostering religious character, cooperation, responsibility, and environmental awareness. The success of P5 implementation is influenced by the support of school principals, teacher commitment, parental involvement, and resource availability. This study provides a concrete contribution to the development of project-based character education practices in elementary schools.